Strengthening of Educational Statistics in India A Synthesis Paper February - 2000 - Planning Commission (Planning Commission Government of India, 2000)
The synthesis paper “Strengthening of Educational Statistics in India,” prepared by the Education Division of the Planning Commission, highlights the urgent need to improve the country’s educational statistical framework. Current data collection is fragmented, with multiple agencies operating without coordination, leading to deficiencies in accuracy, timeliness, and comprehensiveness. Key gaps include irregular data reporting, unrecognized institutions, missing attendance and socio-economic information, and lack of single-age enrollment figures. A Standing Committee on Educational Statistics was established to assess these issues and recommend improvements. The proposed action plan emphasizes regular data collection for school and higher education, establishment of integrated Management Information Systems, and the development of a national policy framework to standardize processes. Strengthening educational statistics is essential for informed policy-making, effective resource allocation, and achieving universal elementary education, providing a roadmap for consolidating efforts into a reliable, cohesive, and strategic national statistical system.
Education Division Planning Commission New Delhi-110001
Education Division Planning Commission New Delhi-110001
Keywords: Educational Statistics; India; Planning Commission; Data Quality; School Education; Higher Education; Management Information Systems; Enrollment Data; Policy Planning; Data Gaps; Statistical Framework; Universal Education